Effect of Molding Pressing Force on the Properties of High-Voltage Porcelain Insulators - Al-Hilli, Muthafar (Iraqi Journal of Science, 2025)
The effect of molding pressing force (1, 2, 3, 4, 5 and 6 tons ) on the properties of 80% kaolin + 20 % soda-lime glass (bottle glass) high voltage porcelain were investigated. The samples were prepared by powder processing technique of semi-dry uniaxial pressing and sintered at 1100oC. Both water absorption % and apparent porosity showed zero value at molding pressing force of 2-3 ton. The linear shrinkage (LS %) was determined by measuring the sample dimensions before and after sintering. The water absorption (WA), apparent porosity (AP) and apparent density (AD) were determined using the vacuum/boiling technique. Vicker’s micro-hardness was measured for the samples. The flexural strength (Rf) was measured by the diametrical compression of a solid disk referred to as the Brazilian disk fracture test. The breakdown voltage of the prepared samples was measured at room temperature.